A Little Hero - Musgrave, H.; Brock, H. M. (Henry Matthew), 1875-1960 (Salt Lake City, UT : Project Gutenberg, 2010)
"A Little Hero" by H. Musgrave is a children's novel written in the late 19th century. The story revolves around the adventures and emotional growth of an eight-year-old boy named Jeff as he navigates the challenges of being separated from his mother and adjusting to life in England after being sent away from India for health reasons. The book captures themes of bravery, responsibility, and the deep bond between a mother and her child. The narrative follows Jeff from his affectionate home in India, where he is cared for by his devoted mother and a nurse, to his journey to England to live with relatives. As he faces the stark contrast of his new environment, he struggles with the dispassionate nature of his relatives and the manipulative behavior of his cousin, Brian. Throughout the story, Jeff exemplifies courage and loyalty, ultimately proving himself a true hero when he risks his life to save Brian from drowning, earning the respect of his relatives. The tale not only showcases Jeff$1 (Bs adventures but also ultimately reflects on enduring love, loss, and the lessons learned in the face of adversity. (This is an automatically generated summary.)s
Release date is 2010-03-04
Produced by Al Haines
Keywords: Boys -- Conduct of life -- Juvenile fiction; Mothers and sons -- Juvenile fiction